Traditional Knowledge of Rattan Crafting in Sepan Village: How the New Capital City Elevates Its Attractiveness - Kuspraningrum, Emilda; Fernhout, Fokke; Putra Kurnia, Mahendra; Erawaty, Rika; Triyana, Lily; Ayu Ratna Sari, Mieke Yustia; Nadia, Nadia; Juniarti, Juniarti (Udayana Journal of Law and Culture, 2025)
Penajam Paser Utara (PPU) Regency in East Kalimantan has been designated as one of the buffer areas of the new Capital City of the Republic of Indonesia, known as Ibu Kota Nusantara (IKN). The Paser tribe, native to PPU Regency, carries rich customs and traditions, one of which is rattan crafting utilizing local materials and traditional knowledge. This article explores opportunities to enhance the attractiveness of PPU Regency through the lens of Cultural Intellectual Property (CIP) in Indonesia. The aim is to raise awareness about developing strategies that strengthen the legal protections for traditional knowledge holders, using CIP to promote Sepan Village's appeal in the context of IKN. The research employs a qualitative approach and utilizes case studies from Sepan Village, PPU Regency. This article suggests that to enhance the allure of this cultural heritage, the PPU Regency government should implement a strategy that involves cataloging the local culture in accordance with the mandates of Law No. 5 of 2017 concerning Cultural Advancement and Government Regulation No. 55 of 2022 concerning Communal Intellectual Property. This strategy should be formalized in regional regulations to provide guidelines for promoting culture and CIP, as well as to clarify the responsibilities of regional government agencies involved in these initiatives.